1997
DOI: 10.1021/ja971151d
|View full text |Cite
|
Sign up to set email alerts
|

First Observation of the Key Intermediate in the “Light-Switch” Mechanism of [Ru(phen)2dppz]2+

Abstract: [Ru(phen)2dppz]2+ (phen = 1,10-phenanthroline, dppz = dipyridophenazine) and closely related complexes have previously been observed to have an undetectably small quantum yield of photoluminescence in water but a moderate emission yield when bound to DNA. This so-called “light-switch” effect is a critical factor in the utility of these complexes as spectroscopic probes for DNA. Here we describe a detailed investigation of the photophysics of [Ru(phen)2dppz]2+ in aqueous solution, and in mixtures of acetonitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
420
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(461 citation statements)
references
References 43 publications
40
420
0
Order By: Relevance
“…D4 were prepared, similarly as reported before for D2 and D6 [8], by condensation of [Ru(phen) 2 (1,10-phenanthrolin-5,6-dione)]Cl 2 with the appropriate substituted benzene-1,2-diamine (see the Supplementary Data).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…D4 were prepared, similarly as reported before for D2 and D6 [8], by condensation of [Ru(phen) 2 (1,10-phenanthrolin-5,6-dione)]Cl 2 with the appropriate substituted benzene-1,2-diamine (see the Supplementary Data).…”
Section: Synthesismentioning
confidence: 99%
“…Ruthenium complexes with dipyridophenazine (dppz) ligands have been frequently studied due to their strong DNA binding and their extraordinary photophysical properties [1,2]. In particular, they have raised a lot of interest due to their "light switch effect" being brightly luminescent when intercalated into DNA and virtually non-emissive in aqueous solution, which is advantageous for use in fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance it is often possible to select a complex with an excited state having an appropriate redox potential or one which shows exquisite sensitivity to its environment. [10][11][12][13][14][15][16][17][18] These properties are particularly valuable for potential therapeutic and diagnostic applications involving the interaction of such complexes with nucleic acids or proteins. [19][20] For example, directed photooxidative damage of nucleic acids opens the possibility of designing a new class of selective antitumour drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In a nonpolar environment, i.e., in the DNA intercalation pocket, the luminescent energy level is lower than that of the non-luminescent level and, therefore, it can be inferred the luminescence develops from the lower energy level, resulting in the "light switch effect". [12][13][14] Direct evidence for the enhancement of the luminescence intensity of the [Ru(phen) 2 DPPZ] 2+ complex by decreasing the solution's polarity was also provided. 11 However, the mechanism for the light switch effect of the [Ru(phen) 2 DPPZ] 2+ complex upon its association with single stranded DNAs is not clear yet, because the single stranded DNA cannot provide any intercalation pocket, i.e., non-polar environment for the incoming Ru(II) complex.…”
Section: +mentioning
confidence: 97%
“…Recent photophysical investigations showed that two energetically close MLCT bands, whose relative energies are sensitive to the environmental polarity, are involved in the light switch mechanism. [11][12][13][14] Although the intercalation of the large DPPZ ligand between the DNA base pair has been deemed to be the origin of the light switch effect, it has recently been reported that the luminescence intensity can also be largely enhanced by the association of the [Ru(phen) 2 DPPZ] 2+ complex with a single stranded DNA which cannot provide any intercalation pocket. 15,16 In the complex formed between [Ru(phen) 2 DPPZ] 2+ and single stranded oligonucleotides, the hydrophobic environment for the [Ru(phen) 2 DPPZ] 2+ complex may be provided by a cavity formed from the single stranded DNA.…”
Section: Introductionmentioning
confidence: 99%